Association of DNA methylation and genetic variations of the APOE gene with the risk of diabetic dyslipidemia. Issue 1 (2022) - EREQAT, SUHEIR; CAUCHI‑, STÉPHANE; EWEIDAT, KHALED; ELQADI, MUAWIYAH; GHATASS, MANAL; SABARNEH, ANAS; NASEREDDIN, ABEDELMAJEED
No abstract available